ANALISIS TINGKAT KEPUASAN PESERTA DIDIK DALAM MENGGUNAKAN E-LEARNING DI SEKOLAH DASAR - Purmadi, Ary; Garnika, Eneng (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2019)
Services in both academic and non-academic very important in achieving learning objectives. The availability of learning facilities consisting of e-learning can be a learning resource that can be used by students in learning. This study aims to analyze the level of participant satisfaction in using e-learning at the elementary school level. The method used is a quantitative method using a questionnaire to respondents. While the learning management system (LMS) used is Edmodo. The sample used was class VI as many as 31 students in SDN 3 Dasan Lekong. The results of the study were as many as 5 people or 16% were very satisfied, 23 people or 74% were satisfied, and 3 people or 10% less satisfied were quite satisfied in using e-learning. While there were no students who stated they were not satisfied in using e-learning. Student satisfaction is a form of desires, hopes and needs of students can be met. This is intended as the desires and expectations of students about the use of e-learning obtained from students' responses have been good.